1997
DOI: 10.2105/ajph.87.4.610
|View full text |Cite
|
Sign up to set email alerts
|

A dietary intervention in primary care practice: the Eating Patterns Study.

Abstract: OBJECTIVES: This study evaluated the effectiveness of a low-intensity dietary intervention in primary care practice in lowering dietary fat intake and raising dietary fiber intake. METHODS: A randomized controlled trial of 28 physician practices in six primary care clinics enrolled, by telephone, adult patients who had appointments for nonurgent nonacute visits. Of 3490 eligible patients contacted, 2111 completed baseline interview; 86.1% also completed a 12-month follow-up. Physicians gave intervention partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 31 publications
2
113
0
2
Order By: Relevance
“…On the other hand, married men and non-married women were less likely to achieve the intended dietary goals, perhaps because married women have generally more responsibility for food purchasing and preparing meals [4] and thus they could more easily adopt the intended changes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, married men and non-married women were less likely to achieve the intended dietary goals, perhaps because married women have generally more responsibility for food purchasing and preparing meals [4] and thus they could more easily adopt the intended changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of the stage of change model as a foundation for lifestyle intervention programs in general practice has been limited. One study involving short interventions of 3 to 5 minutes coupled with written information targeted dietary fat consumption, 20 as did a nonrandomized study of physical activity counseling by physicians. 9 A more extensive trial of physical activity counseling by general practitioners in Australia did not demonstrate any advantage of stage-based programs over routine care, 8 while a recent study of tailored physical activity counseling also showed no differences between intervention subjects and controls in activity levels at 6 weeks or 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…A control group was phone screened and dietary intake was assessed, but no information was provided. A drop in fat intake from baseline was evident in the control and intervention groups post treatment, but greater changes occurred in the intervention group at 3 and 12-month post-treatment assessments (Beresford et al, 1997). Findings indicated that changes in fat intake could occur even in low intensity, public health-based interventions.…”
Section: Other Program Characteristics Impacting Dietary Adherencementioning
confidence: 83%
“…Recent dietary intervention studies have disseminated dietary information in a variety ways, ranging from group counseling (e.g., Schapira et al, 1991) to the distribution of self-help pamphlets (e.g., Beresford et al, 1997).…”
Section: Other Program Characteristics Impacting Dietary Adherencementioning
confidence: 99%
See 1 more Smart Citation